Geographical distribution of antimicrobial exposure among very preterm and very low birth weight infants: A nationwide database study in Japan. - Kota Yoneda; Daisuke Shinjo; Naoto Takahashi; Kiyohide Fushimi (PLoS ONE)
Objectives To examine spatial effects in neonatal care, we conducted a retrospective cohort study to investigate the geographical distribution of antimicrobial exposure among very preterm and very low birth weight infants in Japan. Study design We utilized a nationwide claims database in Japan to extract prescriptions of injectable antimicrobials for 41,423 very preterm and very low birth weight infants admitted within the first two days of life from April 2010 to March 2021. We identified frequently prescribed antimicrobials, revealed early neonatal exposure and neonatal exposure to each antimicrobial agent by 47 prefectures in Japan, and evaluated their spatial autocorrelation using global and local Moran's I statistics. We then scrutinized regional disparities in antimicrobial drug prescriptions. Results The top 10 antimicrobials prescribed to very preterm and very low birth weight infants in Japan were ampicillin, amikacin, gentamicin, cefotaxime, fluconazole, ampicillin combination, micafungin, cefmetazole, cefazolin, and vancomycin. We identified northern cold spots for fluconazole exposure and southern hot spots for ampicillin, amikacin, gentamicin, and cefmetazole exposure. Geographical heterogeneity in the selection of antibacterial and antimycotic agents was observed. Conclusion Our study revealed the geographical distribution of antimicrobial exposure among very preterm and very low birth weight infants in Japan, thus disclosing its spatial effects. Further research addressing the spatial effects of neonatal care is needed to understand how drug exposure affects the outcomes of preterm infants.